(untitled) (Journal on studies and research of academic knowledge, 2016)
This study describes the bioabsorption of bitter orange peel to eliminate iron and lead that are present in effluents. A variation of three physic chemical parameters were used (concentration of metal, size of particles and doses of bio absorbent) assigning two values to each: High and Low. As a result from the variation of parameters, four different experiments were generated for each metal. From the experiments, it was found that for Iron, experiment 3 (pH=4,5, size of particle=0.5mm, concentration of metal=50 mg/L, dose of bio-absorbent =0.5g, time of contact=4h) showed the best percentage for removal (89,65%); whereas, experiment 4 (pH=4,5, size of particle=0.5mm, concentration of metal=30 mg/L, dose of bio-absorbent =0,2g, time of contact=4h) demonstrated a higher absorption capacity (11,08mg of Fe/g of bitter orange peel). The best percentage for the removal of lead was 96,61% and it was obtained in experiment 4 (pH=5, size of particle=0.5mm, concentration of metal=30 mg/L, dose of bio absorbent-0.2g, time of contact=4h), whose capacity for removal was also the best with 14,492 mg of Pb/g of bitter orange peel.